Philosophical Foundation and Urgency of Gender-Equal Islamic Religious Education in Indonesia - Nagita Histimuna Aisyah; Mahfud Junaedi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The formation of a generation that has character and upholds Islamic values can only be obtained through education in which there is a learning and teaching process. Islam itself obliges every believer to study, both men and women. The purpose of this study is to examine the philosophical basis and urgency of gender-equal Islamic Religious Education in Indonesia as a means to produce a generation that carries out its role while still emphasizing morality as well as religious values, both men and women, without exception. This research is a qualitative study with data collection techniques using library research methods that utilize and collect various sources of literature to then examine information relevant to the research topic. The results showed that Islam recognizes the same rights between men and women in getting education. Islamic Religious Education philosophically does not only focus on spiritual aspects but also intellectual. Gender-equal Islamic Religious Education in Indonesia is important to prepare both male and female generations to contribute to building a quality society, in line with the philosophy of Islamic education, which is to equip every human being with knowledge in order to realize their responsibilities and management as the khalifah of Allah.